2016
DOI: 10.2147/jmdh.s105002
|View full text |Cite
|
Sign up to set email alerts
|

The Iranian physicians attitude toward the do not resuscitate order

Abstract: BackgroundPhysicians are responsible for making decisions about the do not resuscitate (DNR) order of patients; however, most of them are faced with some uncertainty in decision making and ethical aspects. Moreover, there are differences on decision making related to the DNR order among physicians, which may be related to the different attitudes toward this issue. Considering the lack of information, this study was performed to investigate doctors’ attitude about DNR order for patients in their final phases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 17 publications
1
25
1
Order By: Relevance
“…The findings of other studies conducted in Iran have indicated that in cases where patients experience terminal illness, dilemma in choosing whether to prolong treatment or allow the normal process of dying to take place is a key challenge for physicians yet is not considered futile (13,14). According to the results of another study in Iran, despite the positive attitude of doctors towards DNR orders, absence of a clear legal guidance regarding this issue leads to various problems in physician's decision-making and necessitates clear instructions/rules from governing bodies in the country (15). Notably, diseases, as one of the factors giving rise to major changes in the lives of people, affect both the patients and their families (16).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of other studies conducted in Iran have indicated that in cases where patients experience terminal illness, dilemma in choosing whether to prolong treatment or allow the normal process of dying to take place is a key challenge for physicians yet is not considered futile (13,14). According to the results of another study in Iran, despite the positive attitude of doctors towards DNR orders, absence of a clear legal guidance regarding this issue leads to various problems in physician's decision-making and necessitates clear instructions/rules from governing bodies in the country (15). Notably, diseases, as one of the factors giving rise to major changes in the lives of people, affect both the patients and their families (16).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also stated that futile therapeutic interventions[ 4 22 ] and the likelihood of CPR failure were some factors affecting decision-making on the DNR order. [ 11 23 ] In other studies, poor medical conditions and prognosis were mentioned as the underlying factors of the DNR order. [ 18 ] In many European countries, when doctors do not believe in the success of CPR or are informed of the CPR's risks, they do not recommend this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] The attitudes of health-care staff including nurses and physicians toward those patients who are spending the final days of their life have always been a major challenge influencing the decision for performing CPR. [ 6 ] This challenge has been perceived in different ways in different countries[ 11 ] because it is influenced by a wide range of cultural, religious, ethnical, and geographical factors. [ 12 ] In this regard, studies conducted in western countries indicted the positive attitudes of health-care professionals toward the DNR order.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general incidence of these resuscitation-related injuries have been reported 21%-65%. 5,6 In the late 1960s, numerous reports regarding the complications of CPR and augmentation and prolongation of patients' suffering, due to the temporary return of physiological stability after resuscitation, were submitted. Considering the presence of a condition in which medical staff believe that resuscitation would not have any benefits, withholding the "resuscitation code" or not proceeding for complete resuscitation, expressions such as "demonstrative code", "slow code", etc.…”
mentioning
confidence: 99%